2021
DOI: 10.25100/cm.v52i1.4437
|View full text |Cite
|
Sign up to set email alerts
|

Genetic markers for preeclampsia in Peruvian women

Abstract: Background: Preeclampsia is a multiorgan disorder associated with maternal and perinatal morbi-mortality. In Peru, incidence is 10% and accounts for 22% of maternal deaths. Genome and genetic epidemiological studies have found an association between preeclampsia and genetic polymorphisms. Objective: To determine the association of the vascular endothelial growth factor (VEGF) +936 C/T and +405 G/C, interleukine-6 (IL-6) -174 G/C, IL-1β-511 C/T, Apo A-1-75 G/A, Apo B-100 2488 C/T (Xbal) polymorphisms with pree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 92 publications
3
6
0
1
Order By: Relevance
“…The incidence of preeclampsia in our study was 10.42%. These results are consistent with previous studies in Peru, where preeclampsia occurs from 5% to 12% of pregnancies [14,15]. Of all patients with preeclampsia, it is estimated that 25% of them will develop severe features [16].…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of preeclampsia in our study was 10.42%. These results are consistent with previous studies in Peru, where preeclampsia occurs from 5% to 12% of pregnancies [14,15]. Of all patients with preeclampsia, it is estimated that 25% of them will develop severe features [16].…”
Section: Discussionsupporting
confidence: 93%
“…Polyphenols are also shown to induce PCDA by inhibiting NO-mediated vasodilatation in pregnant sheep after PRF intake for 14 days [189]. The ductus arteriosus vulnerability to constrictive factors, thus the risk of PCDA, progressively increases with gestational age (e.g., the sensitivity to indomethacin-induced vasoconstriction is approximately 5-10% at 27 weeks, 15-20% at 32 weeks, and almost 100% at 34 weeks [190]. To date, there is no consensus concerning the amount of polyphenol consumption that could cause PCDA.…”
Section: Potential Harmful Effects Of Dietary Polyphenols In Pregnancymentioning
confidence: 99%
“…A recent study demonstrated that PE diagnostic performance using the sFlt-1/PIGF ratio can achieve 95% sensitivity and 91% specificity which is superior to VEGF, PIGF or sFLt-1 [ 55 ]. Lately, several studies have attempted to use the VEGF genetic polymorphisms for early prediction of PE but there remains a lack of clinical competence [ 56 , 57 ].…”
Section: Novel Biochemical Markers With Pe Occurrencementioning
confidence: 99%